2007
DOI: 10.1063/1.2804418
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, pressure, and isotope effects on the structure and properties of liquid water: A lattice approach

Abstract: We present a lattice model to describe the effect of isotopic replacement, temperature, and pressure changes on the formation of hydrogen bonds in liquid water. The approach builds upon a previously established generalized lattice theory for hydrogen bonded liquids [B. A. Veytsman, J. Phys. Chem. 94, 8499 (1990)], accounts for the binding order of 1/2 in water-water association complexes, and introduces the pressure dependence of the degree of hydrogen bonding (that arises due to differences between the molar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 99 publications
5
28
0
1
Order By: Relevance
“…The (solvent-mediated) hydrophobic interaction of solutes is affected by the solvent (water) temperature because the density of the solvent, strength of a hydrogen bonds, and number of hydrogen bonds per molecule are sensitive thereto [13,[25][26][27], -all these characteristics enter the PHB model [15][16][17][18]. They depend on the external pressure (whereto the solvent is subjected) [13,25,26] as well, but this effect was not be considered. The tetrahedral rigidity of the hydrogen bonding armes of a model water molecule was assumed to be unaffected by changing temperature.…”
Section: Discussionmentioning
confidence: 98%
“…The (solvent-mediated) hydrophobic interaction of solutes is affected by the solvent (water) temperature because the density of the solvent, strength of a hydrogen bonds, and number of hydrogen bonds per molecule are sensitive thereto [13,[25][26][27], -all these characteristics enter the PHB model [15][16][17][18]. They depend on the external pressure (whereto the solvent is subjected) [13,25,26] as well, but this effect was not be considered. The tetrahedral rigidity of the hydrogen bonding armes of a model water molecule was assumed to be unaffected by changing temperature.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, the decrease in viscosity was a result of intramolecular hydrophobic associations and variation of M w led to simultaneous variation of electrostatic and hydrophobic interactions (Nichifor, Stanciu, Ghimici, & Simionescu, 2011). Studies on solvents also revealed that, in the case of water, the stability of the hydrogen bonds decreased with increasing temperature (at 300-400 • C, they have disappeared completely) due to the increasing influence of the entropy loss associated with the formation of bonds (Hakem, Boussaid, Benchouk-Taleb, & Bockstaller, 2007;Postorino, Tromp, Ricci, Soper, & Neilson, 1993). Besides, a temperature rise caused a restructuring of the hydrogen bonded network, since the stability of hydrogen bonds decreased, accompanied by a drop (of about 20%) in the number of OH groups that were closely associated (Hakem et al, 2007).…”
Section: Effect Of Autoclave Treatmentmentioning
confidence: 93%
“…Studies on solvents also revealed that, in the case of water, the stability of the hydrogen bonds decreased with increasing temperature (at 300-400 • C, they have disappeared completely) due to the increasing influence of the entropy loss associated with the formation of bonds (Hakem, Boussaid, Benchouk-Taleb, & Bockstaller, 2007;Postorino, Tromp, Ricci, Soper, & Neilson, 1993). Besides, a temperature rise caused a restructuring of the hydrogen bonded network, since the stability of hydrogen bonds decreased, accompanied by a drop (of about 20%) in the number of OH groups that were closely associated (Hakem et al, 2007). Furthermore, the physicochemical properties of large biopolymers were also associated with pH of medium.…”
Section: Effect Of Autoclave Treatmentmentioning
confidence: 94%
“…. 29,30 In subsequent analyses presented below we use the free energy of sliding ΔG sl rather than equilibrium force f eq since the latter quantity is dependent on the spring constant of the particular cantilever used, 24 making direct comparison of values obtained with different cantilevers more difficult. ΔG sl is calculated from the value of f eq and the spring constant of the cantilever used and is therefore directly comparable across different experiments.…”
Section: Resultsmentioning
confidence: 99%